2018
DOI: 10.1002/ccr3.1355
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial subdural abscess with polymicrobial infections due to frontal sinusitis in an adolescent: life‐threatening complication of a common disease

Abstract: Key Clinical MessageIntracranial abscess is one of the most serious complications of frontal sinusitis, particularly among adolescents, even in the absence of odontogenic infection. Polymicrobial infections due to anaerobes are common. Because antibiotic therapy alone is usually ineffective, early endoscopic sinus surgery is the key for infection control and good clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…En cuanto a las complicaciones intracraneales derivadas de una sinusitis con complicaciones poco frecuentes, pero potencialmente graves 2 , las complicaciones craneales más frecuentes son por orden de frecuencia: absceso epidural, empiema subdural, meningitis, encefalitis y absceso cerebral, como en el caso clínico anteriormente descrito 3 . El diagnóstico y manejo de estos pacientes es complejo, y requiere la colaboración de distintos especialistas: otorrinolaringólogos, pediatras, neurocirujanos, neurólogos e internistas entre otros.…”
Section: Discussionunclassified
“…En cuanto a las complicaciones intracraneales derivadas de una sinusitis con complicaciones poco frecuentes, pero potencialmente graves 2 , las complicaciones craneales más frecuentes son por orden de frecuencia: absceso epidural, empiema subdural, meningitis, encefalitis y absceso cerebral, como en el caso clínico anteriormente descrito 3 . El diagnóstico y manejo de estos pacientes es complejo, y requiere la colaboración de distintos especialistas: otorrinolaringólogos, pediatras, neurocirujanos, neurólogos e internistas entre otros.…”
Section: Discussionunclassified
“…However, reports associating sinus infections to the dental region have not been reported. According to Hibi and Amakusa 20 , intracranial infections of sinus origin have been reported and associated with the vascular support present in the region as the infection driving force. Similarly, it is believed that the vascular support present in the sinus region after the rhinoscopy is involved in the infection spread to the periapical region, leading to the development of the acute apical dentoalveolar abscess.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, more studies are needed about intrathecal therapy . Other studies showed that posaconazole and isavuconazole as a second line agent could be used as salvage therapy in no response cases …”
Section: Discussionmentioning
confidence: 99%